Initiation of Nyssomyia neivai and Migonemyia migonei (Diptera: Psychodidae: Phlebotominae) colonies under laboratory conditions from wild blood fed females in northwest Argentina - Copa, G. N.; Almazán, M. C.; Goulart, T. M.; Pinto, M. C. [UNESP]; Marco, D.; Nasser, J. R.; Gil, J. F. (Springer Nature, 2021)
Sand flies (Diptera: Psychodidae: Phlebotominae) are the vectors of Leishmania parasites, which are the causal agents of leishmaniasis. In this work, the survival and developmental time of the immature sand fly stages of Nyssomyia neivai and Migonemyia migonei were studied under laboratory conditions for one generation. Sand flies were collected in a rural dwelling of San Ramón de la Nueva Orán, Salta, Argentina and conditioned in individual rearing containers at 25±2 °C and 80–90% humidity. A total of 38 females of Ny. neivai oviposited 1,392 eggs (x ¯ = 40.81±16.5) in 5.6 days whereas two females of Mg. migonei oviposited 119 eggs (x ¯ = 59.50±4.95) in seven days. Migonemyia migonei presented a higher hatching percentage (66.39%) than Ny. neivai (60.99%), without statistical differences between the species (p > 0.05). A total of 78 adults of Ny. neivai emerged (5.60%) while 27 adults (22.69%) emerged for Mg. migonei (p < 0.0001). The survival curves of both species showed that the mortality decreased in the last stages and tended to constant values. This is the first study about the life cycle of sand flies present in northern part of province of Salta, the most endemic area of tegumentary leishmaniasis in Argentina. These results would allow the sustained study of sand flies in the laboratory to deepen the knowledge and understanding of their biology. Finally, it would contribute to elucidate the epidemiological role of the most abundant sand fly species in our study area where Leishmania (Viannia) braziliensis prevails.
Keywords: Argentina; Leishmaniasis; Life cycle; Phlebotominae; Psychodidae; Sand fly